Representing search tasks in an information use environment: a case of English primary schools. Issue 6 (26th September 2019) - Rutter, Sophie; Toms, Elaine G.; Clough, Paul David
Abstract : Purpose: To design effective task-responsive search systems, sufficient understanding of users' tasks must be gained and their characteristics described. Although existing multi-dimensional task schemes can be used to describe users' search and work tasks, they do not take into account the information use environment (IUE) that contextualises the task. The paper aims to discuss these issues. Design/methodology/approach: With a focus on English primary schools, in four stages a multi-dimensional task scheme was developed that distinguishes between task characteristics generic to all environments, and those that are specific to schools. In Stage 1, a provisional scheme was developed based upon the existing literature. In the next two stages, through interviews with teachers and observations of school children, the provisional scheme was populated and revised. In Stage 4, whether search tasks with the same information use can be distinguished by their characteristics was examined. Findings: Ten generic characteristics were identified (nature of work task, search task originator, search task flexibility, search task doer, search task necessity, task output, search goal, stage in work task, resources and information use) and four characteristics specific to primary schools (curricular area, use in curricular area, planning and location). For the different information uses, some characteristics are more typical than others. Practical implications: The resulting scheme, based on children's real-life information seeking, should be used in the design and evaluation of search systems and digital libraries that support school children. More generally, the scheme can also be used in other environments. Originality/value: This is the first study to develop a multi-dimensional task scheme that considers encompasses the IUE.